ADVERSITY QUOTIENT®, EMOTIONAL QUOTIENT AND ACADEMIC PERFORMANCE OF FILIPINO STUDENT-PARENTS - Yazon, Alberto D; Ang- Manaig, Karen (PEOPLE: International Journal of Social Sciences, 2020)
This study is descriptive-correlational research aimed to determine the significant relationship between Emotional Quotient, Adversity Quotient®, and the Academic Performance of Student-Parents. Chi-Square Test was utilized to test the significant relationship among variables. Purposive sampling was employed since there are only thirty (30) identified student-parents enrolled in the university. The General Weighted Average (GWA) during the second semester of AY 2016-2017 of the respondents was used to determine their academic performance. Based on the findings of the study, the majority of the student-parents are in their late 20’s and early 30’s, female, Education students, in their lower year, and have 1 – 2 children. These results suggest that the student-parents are in their matured ages since almost all of them are returnees. The respondents reported that they have a high level of emotional quotient. Therefore, the study revealed that there is no significant relationship among student-parents’ emotional quotient, adversity quotient, and academic performance. Hence, researchers fail to reject the null hypothesis. The researchers strongly recommended that the university should devise a program for student-parents dealing with life adversities. Similar studies may be conducted to explore more studies concerning adversity quotient® using other variables not included in this study.